Anacardium occidentale-induced cutaneous reaction: a rare presentation of irritant contact dermatitis - Dhavalshankh, Ganesh; Dhavalshankh, Gayatri; Goyal, Sagar; Dhavalshankh, Archana; Sheetal (International Journal of Research in Dermatology, 2025)
Cashew apples, obtained from the Anacardium occidentale tree, are widely used in food preparation across tropical regions like India. While raw cashew apples are generally regarded as edible, it's important to be aware that they can carry some unanticipated skin risks. This is primarily due to the presence of irritants such as anacardic acid, cardol, and cardanol that can affect the skin. These substances, chemically related to urushiol (found in poison ivy), are known to trigger irritant contact dermatitis (ICD). We present a case of a 40-year-old housewife who developed sudden-onset skin inflammation after handling raw, wet cashew apples for the first time. Within 20 minutes, she experienced intense itching, redness, swelling, and blistering on her hands and forearms. The lesions progressed to bullae with serous discharge, typical of ICD. There was no prior history of allergies or dermatological conditions. The patient responded well to systemic corticosteroids (Omnocortil), antibiotics (Roxithromycin), antihistamines, and topical mupirocin. This case highlights the need for greater public and clinical awareness about the dermatotoxic potential of cashew apple exposure in non-industrial settings. Preventive measures, such as using gloves and minimizing skin contact, are crucial when handling cashew products. Clinicians should maintain a high index of suspicion for plant-based irritants in patients presenting with acute dermatitis and a clear exposure history.